Relationship between starting up unregistered and firm performance in Sub-Saharan Africa: Does duration matter? - Matsitse, Kgalalelo (University of the Witwatersrand, Johannesburg, 2024)
This paper investigates whether start-up firms that remain unregistered for longer outperform their peers in the long run. It hypothesises that the benefit of staying unregistered is non-linear in time and depends on institutional context. This paper considers the relationship between years spent unregistered and employment productivity growth in the informal sectors of Nigeria, Kenya and South Africa, highlighting the significant role of institutional contexts in shaping entrepreneurial decisions and firm performance (Williams, Martinez-Perez, & Kedir, 2017; Assenova & Sorenson, 2017; Autio & Fu, 2015; Galdino, Molina- Sieiro, Lamont, & Holmes Jr, 2023). World Bank Enterprise Survey data was analysed using linear multivariate regression analysis, which enabled examination of the relationship between years spent unregistered and firm employee productivity growth, determining its statistical significance while controlling for other independent variables. The findings underscore the heterogeneity of this relationship across developing countries. This suggests that policymakers must consider distinct institutional environments to foster economic growth and achieve Sustainable Development Goal 8; which aims to promote sustained, inclusive, and sustainable economic growth, full and productive employment, and decent work for all (United Nations, 2023).
A research report submitted in fulfillment of the requirements for the Master of Commerce (Applied Development Economics), In the Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; FIRM PERFORMANCE; SDG-8: Decent work and economic growth